RESOLYING AMBIGUITIES OF MEANING FROM CONTEXTUAL CLUES IN POLISH TEXTS - Krezolek, Marek (Computer Science, 2020)
This article describes a Computer programme designed to assign the appropriate meaning to homonyms based on the context in which they appear. Homonyms can be defined as words with a number o f dijferent, often unrelated, meanings (for example a bank - a business that lends or keeps money, the land along the side o f river, a large pile o f earth, sand, snów). The programme described in the paper exploits a monolingual dictionary, which, together with and supported by declension dictionary assigns the appropriate meaningfor any given wordfrom the text. In order to assign the correct and appropriate meaningfor the given context two methods are used and exploited: 1) Recognition o f the meaning o f a particular homonym based on the occurrence o f its collocations in the immediate context. 2) Applying the correct meaning o f the word based on the overall theme or topie o f the text in which appears.